Non-Specific Gastric Inflammation in Children is Associated with Proton Pump Inhibitor Treatment for More than 6 Weeks - Rosas-Blum, Eduardo D.; Tatevian, Nina; Rhoads, Jon M.; Hashmi, Syed S.; Navarro, Fernando (Frontiers in Pediatrics, 2014)
Background & Aims: Non-specific gastric inflammation (NSGI) is a commonly reported pathological finding. We investigated if it is associated with the use of proton pump inhibitors (PPI) in children at a single tertiary center. Methods: We performed an IRB-approved chart review of all endoscopy and biopsy reports of patients who underwent esophagogastroduodenoscopy between July 2009 to July 2010 (n=310). Demographic data, dose, and duration of exposure to PPI, and biopsy results were collected and analyzed. All esophageal, gastric and duodenal biopsies were independently reviewed by a pathologist. Patients with acute gastritis, moderate/severe chronic gastric inflammation or Helicobacter pylori infection were excluded. The presence of NSGI was compared between patients exposed and not exposed to PPI as well as between patients with different doses and durations of PPI exposure to assess for potential associations. Results: A total of 193 patients were included: 88 (46%) had a history of PPI use, and 48 (25%) were found to have NSGI. Compared to patients not exposed to PPI, the odds ratio of NSGI in patients exposed to PPIs was 2.81(95% CI: 1.36-5.93). The odds ratio of NSGI in patients exposed to PPI for >3 months was 4.53(95% CI: 1.69-11.97). Gender, ethnicity, and age were not associated with NSGI. No histological differences were found in the esophagus and duodenum between patients exposed and not exposed to PPI. Conclusion: This study found that PPI exposure is associated with NSGI with a higher risk for those exposed for >3 months. As the clinical implications of NSGI are not known, judicious use of PPIs is needed. Prospective studies are required to confirm and to determine the etiologic factors (i.e. alteration of the gastric pH, serum gastrin) that may be related with the presence of NGSI.